Fetal Outcome in Cesarean Versus Normal Deliveries in Pregnancy with Meconium-stained Liquor: A Cross-sectional Study - Jha, Umesh Chandra; Dangal, Ganesh (Journal of Nepal Health Research Council, 2021)
Background: Intrauterine meconium passage in near term or term fetuses has been associated with feto-maternal stress factors and/or infection and is contributing to the increased rate of cesarean section. This study aimed to evaluate effect of mode of delivery on fetal outcome in pregnancy with meconium-stained liquor.Methods: A cross sectional study was done in 2019 at a tertiary care center. Data was collected from women in labor, in whom meconium was seen after rupture of membrane. Out of these, 115 cases, who underwent cesarean delivery for meconium-stained liquor were enrolled in one group; while in another group 115 cases who delivered vaginally were enrolled and the fetal outcome was compared in between these two groups.Results: Out of 230 cases, most participants were from 21 to 25 years age group. Most of patients were primigravida accounting for 63%, and with mean gestational age of 39.4 weeks. Low Apgar score at one and 5 minutes, percentage of respiratory distress, perinatal asphyxia, need of bag and mask ventilation as mode of resuscitation were associated more with vaginal deliveries. Incidence of Neonatal Intensive Care Unit admission, meconium aspiration syndrome, and neonatal death were seen more in vaginal delivery in comparison to cesarean delivery.Conclusions: There was no much difference in Apgar score at 5 minutes in either mode of delivery. Incidence of respiratory distress, perinatal asphyxia, Neonatal Intensive Care Unit admission, meconium aspiration syndrome and neonatal death were higher in vaginal delivery. Fetal morbidity and mortality were seen more in moderate to thick meconium-stained liquor.Keywords: Cesarean section; fetal outcome; meconium-stained liquor; vaginal delivery